2006
DOI: 10.3998/ark.5550190.0007.b04
|View full text |Cite
|
Sign up to set email alerts
|

One-pot rapid and efficient synthesis of new spiro derivatives of 11H-indeno[1,2-b]quinoxalin-11-one, 6H-indeno[1,2-b]pyrido[3,2-e]pyrazin-6-one and isatin-based 2-pyrazolines

Abstract: Some new spiro derivatives (5a-h, 9a-c and 13a-c) of 11H-indeno[1,2-b]quinoxalin-11-ones 1a-b and 6H-indeno[1,2-b]pyrido[3,2-e]pyrazin-6-one 6 and isatin 10 were synthesized by two different pathways. The chalcones 4a-h, 8a-c and 12a-c were prepared by the reaction of acetophenone and its four derivatives with 1a-b, 6 and 10 via base-catalyzed condensation followed by addition of acid. In the first procedure, the chalcones were isolated and reacted with hydrazine hydrate to give products. In the second procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previously, the same research group also reported the synthesis of spiro-indenoquinoxalinepyrazolines 6, separately by the reaction of chalcones 4 and hydrazine hydrate. 24 indenoquinoxaline 11 via four-component reaction of ninhydrin 1, benzene-1,2-diammine 2, tert-butyl isocyanide 10, and dialkylacetylenedicarboxylates 9 in dry CH 2 Cl 2 at room temperature in 8 h. In this process the intermediate indenoquinoxalinones 3 were generated in situ from the reaction of ninhydrin 1 and benzene-1,2-diamines 2 (Scheme 5).…”
Section: Generation Of a Three-membered Ring On The Indeno[12-b]quinoxaline Moietymentioning
confidence: 99%
“…Previously, the same research group also reported the synthesis of spiro-indenoquinoxalinepyrazolines 6, separately by the reaction of chalcones 4 and hydrazine hydrate. 24 indenoquinoxaline 11 via four-component reaction of ninhydrin 1, benzene-1,2-diammine 2, tert-butyl isocyanide 10, and dialkylacetylenedicarboxylates 9 in dry CH 2 Cl 2 at room temperature in 8 h. In this process the intermediate indenoquinoxalinones 3 were generated in situ from the reaction of ninhydrin 1 and benzene-1,2-diamines 2 (Scheme 5).…”
Section: Generation Of a Three-membered Ring On The Indeno[12-b]quinoxaline Moietymentioning
confidence: 99%
“…An aldol-addition of acetophenones 312 to isatin 1 affords 3-hydroxy-3-phenacyloxindoles 313 which undergoes dehydration forming 3-phenacylidene-2-oxindoles 314 in quantitative yields that have been employed in the synthesis of spiro-dihydropyrimidinethione-oxindole 315 and spiro-pyrazoline-oxindoles 316 – 317 . , The reaction of compound 314 with phenylthiourea afforded the product 315 , whereas the reactions with phenylhydrazine and with hydrazine resulted in the formation of N -phenylpyrazoline 316 and pyrazoline 317 , respectively, spiro-fused to 2-oxindole (Scheme ).…”
Section: Synthesis Of Isatin-based Spiro-fused Heterocyclic Frameworkmentioning
confidence: 99%
“…Several strategies have been developed to prepare pyrazoline-spirooxindoles. One strategy is through amination/Michael reaction of chalcone-derived oxindoles and hydrazine hydrate, 4 but the asymmetric version of this method has not been attained yet (Scheme 1B-a). Another one is through [3 + 2] cycloaddition of alkenyloxindoles with α-diazocarbonyl compounds or nitrile imines as C 3 synthons.…”
Section: Introductionmentioning
confidence: 99%